Feasibility of increased biogas production from the co-digestion of agricultural, municipal, and agro-industrial wastes in rural communities. Issue 4 (29th April 2008) - McDonald, Tanya; Achari, Gopal; Abiola, Abimbola
Abstract : In rural communities, such as Olds, Alberta (population 7248) energy may be produced through anaerobic co-digestion of municipal, agricultural, and agro-industrial wastes. An inventory within a 20 km radius of Olds revealed that 291 000 tonnes of wet organic waste are generated annually (96.8% manure) with an electrical potential of 42 GWh (1 GWh = 10 6 kWh). Analysis of feedlot, hog, dairy and poultry manure, offal, food, grass, and biosolids identified the potential for waste blending to optimize solids content, nutrient balance, and pH level. In laboratory tests, biogas yield increased from 0.382 m 3 /kg volatile solid (VS) for feedlot manure alone to 0.513, 0.517, and 0.500 m 3 /kg VS with co-digestion of 30% hog manure, 15% offal, and 30% offal, respectively. Methane content of biogas increased from 75.8% in feedlot manure digestion to 78.8, 79.5, and 80.9% with co-digestion of 30% hog manure, 15% offal, and 30% offal, respectively.